Measurements of height and weight and their impact on the direction of the submission students in the department of physical education in Baya morning institute of preparing teachers. - Majeed, Assel (Journal of Physical Education, 2014)
The research included five parts, in 1st part, the researcher mentioned of the importance of research, presentation of the problem, and installs the objectives mentioned areas of research. 2nd part has included theoretical studies which were in regard to the subject. 3rd part, the researcher dealt with the research methodology and procedures, the research method was a survey, then she across the research sample with details and the method chosen, then she mention to equipment and the tools which used to research and measurements of height, weight, and direction. At the end of this part the researchers mention the means of statistical which used in the search. Part 4th the researchers offered from the results obtained through them and they analyzed and discussed these results. In Part 5th the researchers showing conclusions obtained from the analysis and discussion of results and finally the researchers mention some of the recommendations that came on regarding what the researchers concluded.